2016
DOI: 10.7494/csci.2016.17.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Tree Structures for Adaptive Control Space in 3d Meshing

Abstract: The article presents a comparison of several octree-and kd-tree-based structures used for the construction of control space in the process of anisotropic mesh generation and adaptation. The adaptive control space utilized by the authors supervises the construction of meshes by providing the required metric information regarding the desired shape and size of elements of the mesh at each point of the modeled domain. Comparative tests of these auxiliary structures were carried out based on different versions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As in [16], it has been shown that kd-trees are useful for constructing control space structures. This time, the focus was on the introduction of discrete metric sources into these structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in [16], it has been shown that kd-trees are useful for constructing control space structures. This time, the focus was on the introduction of discrete metric sources into these structures.…”
Section: Discussionmentioning
confidence: 99%
“…The auxiliary structures dedicated to this purpose may have the form of a Cartesian mesh (either homogeneous [21] or adapted [3]), background mesh [7,19,20,23], or quadtree/octree [18,22,23]. Recently, the application of a kd-tree was also proposed by the authors of [16]. Each of these structures has its advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation